Effects of Zinc, Iron and Copper Supplementation in Cassava-Based Diets for Broiler Chickens - Phuahi, C. H.; Hutagalung, R. I. (1980)
Two experiments involving 216 chicks were conducted to assess the effects of supplemental levels of zinc (0, 25, 50 ppm) in combination with iron (0, 25, 50 ppm) in Experiment 1 and with copper (0, 5, 10 ppm) in Experiment 2, in diets containing cassava (40%) and protein (20-17%). The dietary treatments were arranged in a 3 X 3 factorial experiment. Mineral supplementation in cassava-based diets had little overall effect on rate and efficiency ofgain. In~lusion of increasing amounts of zinc in combination wi!h iron or copper had inconsistent effects on fat and protem content of the carcass. Chzeks fed cassava-based dzets supplemented with iron showed less carcass zinc levels, but had higher liver zinc content than those fed diets unsupplemented with iron. Raising the zinc content of the diet resulted in reducing copper retention in the liver, regardless of its combination with iron and copper.